Clinicopathological and prognostic significance of SOX9 expression in gastric cancer patients: A meta-analysis. Issue 37 (16th September 2022) - Wang, Qian; Chen, Hao; Yang, Congying; Liu, Yi; Li, Feng; Zhang, Chunfang
Abstract : Background: SOX9 is a potential prognostic marker in gastric cancer (GC) patients. This meta-analysis aimed to highlight the clinicopathological and prognostic implications of SOX9 expression in GC patients. Methods: A systematic literature search was conducted to identify relevant studies by the electronic literature databases (PubMed, Web of Science, EMBASE and Chinese databases). Review Manager version 5.4 was employed to evaluate the pooled odds ratio (OR) or hazard ratio (HR) with 95% confidence intervals (CIs). Results: Seventeen studies with a total of 2893 GC patients were enrolled in this meta-analysis. The analysis with ten articles clarified that higher expression of SOX9 was observed in GC cancers than that of normal gastric samples (OR = 16.26; 95% CI: 8.16 to 32.42; P  < .00001). Consequently, the results also showed that SOX9 expression was closely associated with age (OR = 1.34; 95% CI: 1.04–1.72; P  = .03), tumor size (OR = 0.67; 95% CI: 0.49–0.91; P  = .01), histological differentiation (OR = 0.62; 95% CI: 0.36–1.06; P  = .002), tumor stage (OR = 0.48; 95% CI: 0.20–1.12; P  = .04), lymph node metastasis (OR = 0.36; 95% CI: 0.19–0.67; P  = .0010) and advanced TNM stage (OR = 0.46; 95% CI: 0.30–0.70; P  = .0003), but not significantly related to gender, distant metastasis and vascular invasion. Furthermore, high SOX9 expression could significantly indicate poorer overall survival (OS) (HR = 1.40; 95% CI: 1.14–1.72; P  = .001). Conclusion: SOX9 overexpression might be related to poor prognosis and could serve as a potential predictive marker of poor clinicopathological prognosis factor in GC patients.